Augmented Reality User Interfaces in Home User Applications - Vikström, Meri (2003)
Jyväskylä, University of Jyväskylä, 2003. Abstract: Augmented Reality is an area of Mixed Reality where virtual images are superimposed upon the real environment the user sees. This survey studies, based on previous work, the possibilities for creating Augmented Reality user interfaces for home user applications. Different ways of creating Augmented Reality user interfaces and different types of Augmented Reality applications are introduced and possible home user Augmented reality applications are discussed.